2023
DOI: 10.18240/ijo.2023.07.19
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, radiological imaging, and treatment strategies of nonmetallic intraorbital foreign bodies: a retrospective analysis

Abstract: AIM: To provide comprehensive data on nonmetallic intraorbital foreign bodies (IOFBs) by summarizing and analyzing material types, clinical manifestations, imaging features, and treatment strategies. METHODS: Totally 28 nonmetallic IOFB cases treated at Shengjing Hospital of China Medical University from 2012 to 2020 were retrospectively reviewed. The types of foreign bodies, clinical features, imaging manifestations, and treatment outcomes were analyzed. RESULTS: Among all cases, 67.8% (19/28) of the foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is necessary to protect the eyes, strengthen eye hygiene, and have regular eye examinations for the prevention of ophthalmic diseases. Some studies have also found that setting off fireworks and firecrackers can easily cause eye injuries [ 2 , 33 ]. It is necessary not only to protect one’s safety but also to strengthen the awareness of eye protection for people involved in dangerous work, such as fireworks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to protect the eyes, strengthen eye hygiene, and have regular eye examinations for the prevention of ophthalmic diseases. Some studies have also found that setting off fireworks and firecrackers can easily cause eye injuries [ 2 , 33 ]. It is necessary not only to protect one’s safety but also to strengthen the awareness of eye protection for people involved in dangerous work, such as fireworks.…”
Section: Discussionmentioning
confidence: 99%